(untitled) (International Journal of Engineering and Computer Science, 2017)
This paper presents a specially designed cascaded H bridge multilevel inverter to increase the number of levels with reduced no of switches and best suited for medium voltage drive applications. An efficient approach to the voltage balancing issue is addressed by implementing third harmonic injection. To enhance the balanced distribution of power in each cell, Multi carrier phase shifted pulse width modulation switching scheme is employed. The midpoint capacitor voltage in unit cells is achieved with total harmonic injection method. This new topology of inverter offers less amount of THD when comparing with the conventional one. The validity of the proposed inverter is verified through MATLAB Simulink model and the scaled down prototype model is implemented in hardware.